Characterization of bioactive substances MHGF-68 on tumour cell lines with LiveFlow In Vitro Technology - Hodoši R. (Sciendo, 2021)
As part of experimental research, growth factor-like substances associated with MHV-68, named MHGF-68, were discovered in our laboratory. MHGF-68 activity was manifested by the ability to alter cell morphology, that is, normal phenotype to transformed, resp. suppresses the transformed phenotype of tumour cells. The aim of the experiments was to monitor the effect of MHGF-68 on the change of the cell actin cytoskeleton in the tumour cell line Hepa1c1c7, as well as the normal cell line NIH3T3, and compare conventional stationary cultivation and dynamic cultivation conditions using a LiveFlow system (In Vitro Technologies). LiveFlow is an advanced system to test the impact of different compounds on the cell cultures, which allows simulation of in vivo conditions thanks to continuous flow of cultivation medium. MHGF-68 was prepared with the infection of BHK-21 cells with MHV-68 virus under non-permissive conditions (41°C). After dynamic cultivation with MHGF-68, we observed changes in morphology on Hepa1c1c7 cells. In cells cultured in a dynamic environment, we observed more pronounced changes in cell morphology in comparison with cells cultured statically. We observed no changes in the cytoskeletal structures in the NIH 3T3 cell line affected by MHGF-68 in both types of cultivation. The advantage of LiveFlow in comparison to in vivo testing is that the experiments performed in this system are less time and money consuming. Dynamic cultivation in the LiveFlow system is suitable for optimizing experiments before testing substances in vivo.